General Pratitioner: Poster Presentation - Observational Study - General practitioner - dr. Giovani; Heryanti, dr. Carla Oktavia (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Glaucoma is disturbance of part or all of the visual field caused by damage to the optic nerve and increased intraocular pressure, and obstruction of the outflow of aqueous humor, which can lead to complete blindness. Primary angle-closure glaucoma (PACG) is a common cause of blindness. PACG affects more than 17 million people worldwide. This study aimed to provide prevalence of primary angle-closure glaucoma patients at Marianum General Hospital, Halilulik, Indonesia. Methods : This research was a descriptive observational study with secondary data, where there were 21 research subjects. This study presents clinical, sociodemographic, and management data of angle- closure glaucoma patients. Data analysis was carried out univariately with SPSS. Results : The majority of angle-closure glaucoma patients are older than 40 years old. Mens are found less likely to have PACG than woman. First degree relatives with glaucoma disorders has not provided optimal data in this study. The majority of glaucoma patients in this study have intraocular pressure ? 21 mmHg. The majority of research subjects do not have refractive disorders. The majority of patients receive medical therapy in the form of 2 types of eye drops. Conclusion : Primary angle-closure glaucoma (PACG) is the second most common for of Glaucoma that cause irreversible blindness. Early diagnosis is very important to prevent blindness. The majority of angle- closure glaucoma patients at Marianum General Hospital, Halilulik, Indonesia, have normal intraocular pressure without refractive errors and receive combination therapy of 2-3 eye drops.